2014
DOI: 10.1186/1752-1947-8-67
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya – an emerging infection in Bangladesh: a case series

Abstract: IntroductionChikungunya is an arthropod-borne virus endemic to Africa, Southeast Asia and India that causes acute febrile polyarthralgia and arthritis. In this short case series, we discuss six Bangladeshi patients with chikungunya fever. Though Bangladesh is in endemic zone, it is not common here, hence it demands attention for proper diagnosis and management.Case presentationThe six cases of chikungunya we report occurred in native Bangladeshi women with ages ranging from 20 to 50 years and all having a midd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 8 publications
2
33
0
1
Order By: Relevance
“…In fact, this disease manifestation is so common in CHIKV-induced disease, it has been reported that the presence of concurrent high fever and arthralgia has a specificity of 99.6% and positive predictive value of 84.6% for the diagnosis of CHIKV infection [38]. However, it should be noted that other arboviruses such as dengue, Zika, and other alphaviruses can have similar clinical presentations, including fever and arthralgia.…”
Section: Joint Diseasementioning
confidence: 99%
“…In fact, this disease manifestation is so common in CHIKV-induced disease, it has been reported that the presence of concurrent high fever and arthralgia has a specificity of 99.6% and positive predictive value of 84.6% for the diagnosis of CHIKV infection [38]. However, it should be noted that other arboviruses such as dengue, Zika, and other alphaviruses can have similar clinical presentations, including fever and arthralgia.…”
Section: Joint Diseasementioning
confidence: 99%
“…In 1999, in Chittagong Medical College Hospital, a young boy was suspected to have chikungunya (Personal communication Prof M A Faiz). A case series of 6 chikungunya was reported in 2013 27 . Another review was reported in next year with updated information.…”
Section: Bangladesh Situationmentioning
confidence: 99%
“…[1][2][3] The name is derived from the Mekonde word meaning 'that which contorts or bends up' in reference to the stopped posture developed as a result of the arthritic symptoms of the disease. 4 Chikungunya virus or CHIK virus is a Group IV (+) RNA virus belonging to family Togaviridae, Genus Alphavirus and species Cikungunya virus.…”
Section: Introductionmentioning
confidence: 99%